Structural and elastic properties of BiOCu0.875S with Cu vacancies : A First principles study - LAKEL, Saïd; IBRIR, M.; GUIBADJ, A. (Science des matériaux (Laboratoire LARHYSS); Vol. 6 (2015): Vol. 5 (2015): Science des matériaux (Laboratoire LARHYSS) (Novembre), 2008)
The  structural and elastic properties of BiOCu 0.875 S with Cu vacancies have been investigated by using the first-principles density functional theory within the generalized gradient approximation. Population  analysis  suggests  that  the  chemical  bonding  in  BiOCu 0.875 S  has  predominantly  ionic  character  with  mixed covalent−ionic character. Basic physical properties, such as lattice constant, elastic constants C ij , bulk modulus B, shear modulus G, were calculated.  The  elastic  modulus E and  Poisson  ratio ν  the ratio B/G, shear anisotropy  and elastic anisotropy β c /β a  were  also  predicted.  The  results  show  that  tetragonal  phase  BiOCu 0.875 S  is mechanically stable and behaves in a ductile manner.